Balloon Dilation of the Eustachian Tube: 12‐Month Follow‐up of the Randomized Controlled Trial Treatment Group. (8th January 2019) - Anand, Vijay; Poe, Dennis; Dean, Marc; Roberts, William; Stolovitzky, Pablo; Hoffmann, Karen; Nachlas, Nathan; Light, Joshua; Widick, Mark; Sugrue, John; Elliott, C. Layton; Rosenberg, Seth; et al.
Abstract : Objective: Obstructive eustachian tube dysfunction (OETD) affects up to 5% of adults; however, available treatment strategies have limitations. It was previously reported that balloon dilation of the eustachian tube (BDET) with the eustachian tube balloon catheter + medical management (MM) results in a significantly higher proportion of subjects with normalized tympanograms versus MM alone at 6‐ and 24‐week follow‐up. The current analysis extends these initial findings by investigating the durability of BDET + MM treatment outcomes through 52 weeks. Study Design: Prospective cohort follow‐up study from the treatment group in a previously reported multicenter randomized controlled trial. Setting: Twenty‐one investigational sites across the United States. Subjects and Methods: Here we report on secondary and exploratory endpoints for patients with OETD who previously failed MM and were randomized to the BDET + MM cohort. Analyses of tympanogram outcomes are reported by ear, unless specified otherwise, as a more accurate measure of durability of the procedure over time. Results: Among subjects randomized to BDET + MM, the overall number with normalized tympanograms and ETDQ‐7 scores (Eustachian Tube Dysfunction Questionnaire–7) remained comparable to those reported at 6‐ versus 52‐week follow‐up: tympanograms, 73 of 143 (51.0%) versus 71 of 128 (55.5%); ETDQ‐7, 79 of 142 (55.6%) versus 71 of 124 (57.3%). The overall number of ears with normalized tympanograms also remained comparable, with 117 of 204 (57%) versus 119 of 187 (63.6%). Conclusions: The present study suggests that the beneficial effects of BDET + MM on tympanogram normalization and symptoms of subjects with refractory OETD demonstrate significant durability that is clinically relevant through 52 weeks.